Control on teams: a model and empirical evidence from Bulgaria - Lambovska, Maya Rumenova (Serbian Journal of Management, 2018)
This paper suggests an original model for control on teams. The originality of the model is associated with a combination of management concepts and mathematical theories of fuzzy logic and fuzzy sets. In addition to the team control model, the author proposes a toolkit for measurement and evaluation of team performance. The toolkit incorporates fuzzy techniques and tools for quantification of evaluations, decision-making, study of joint influences and hidden effects. The results from testing the team control model at a Bulgarian University are also presented and discussed in this paper.
Keywords: team; control; fuzzy logics; performance evaluation; modelling; Bulgaria